THE FIRST FIND OF (BA, V) MICAS IN THE URALS - Korinevsky V.G.; Korinevsky E.V. (My University, 2006)
(Ba,V) micas are rather rare. Reports about their occurrence in the Urals are unknown to date. We found these micas in igneous and metamorphic rocks of the Il’menskie Gory (Ilmeny Mountains) Complex and its framework in the southern Urals.
Keywords: (Ba,V) micas; Urals